CD206+ M2-Like Macrophages Are Essential for Successful Implantation - Ono, Yosuke; Yoshino, Osamu; Hiraoka, Takehiro; Sato, Erina; Fukui, Yamato; Ushijima, Akemi; Nawaz, Allah; Hirota, Yasushi; Wada, Shinichiro; Tobe, Kazuyuki; Nakashima, Akitoshi; Osuga, Yutaka; et al. (Frontiers in Immunology, 2020)
Macrophages (MΦs) play important roles in implantation. Depletion of CD11b+ pan-MΦs in CD11b-diphtheria-toxin-receptor (DTR) mice is reported to cause implantation failure due to decreased progesterone production in the corpus luteum. However, of the M1 and M2, the type of MΦs that is important for implantation is unknown. In this study, we investigated the role of M2 MΦ in implantation using CD206-DTR mice. To deplete M2-MΦ, female CD206-DTR C57/BL6 mice were injected with DT before implantation. These M2-MΦ depleted mice (M2(-)) were naturally mated with Balb/C mice. As the control group, female C57/BL6 wild type (WT) mice injected with DT were mated with male Balb/C mice. The number of implantation sites and plasma progesterone levels at implantation were examined. Implantation-related molecule expression was determined using quantitative-PCR and immunohistochemistry of uterine tissues. The mRNA expression in the endometrial tissues of 38 patients with implantation failure was examined during the implantation window. In WT mice, CD206+M2-like MΦs accumulated in the endometrium at the implantation period, on embryonic (E) 4.5. In M2(-), the implantation number was significantly lower than that in control (p < 0.001, 7.8±0.8 vs. 0.2±0.4), although the plasma progesterone levels were not changed. Leukemia inhibitory factor (LIF) and CD206 mRNA expression was significantly reduced (p < 0.01), whereas the levels of TNFα were increased on E4.5 (p < 0.05). In M2(-), the number of Ki-67+ epithelial cells was higher than that in control at the pre-implantation period. Accelerated epithelial cell proliferation was confirmed by significantly upregulated uterine fibroblast growth factor (FGF)18 mRNA (P < 0.05), and strong FGF18 protein expression in M2(-) endometrial epithelial cells. Further, M2(-) showed upregulated uterine Wnt/β-catenin signals at the mRNA and protein levels. In the non-pregnant group, the proportion of M2-like MΦ to pan MΦ, CD206/CD68, was significantly reduced (p < 0.05) and the TNFα mRNA expression was significantly increased (p < 0.05) in the endometrial tissues compared to those in the pregnant group. CD206+ M2-like MΦs may be essential for embryo implantation through the regulation of endometrial proliferation via Wnt/β-catenin signaling.